Expanded Endoscopic Approach for Anterior Skull Base Tumors: Experience of a Multidisciplinary Skull Base Team. Issue 6 (September 2019) - Marchioni, Daniele; Gulino, Antonio; Sacchetto, Luca; Pinna, Giampietro; Musumeci, Angelo; Molteni, Gabriele
Abstract : Abstract: The aim of this study is to describe the experience of a multidisciplinary skull base team with transnasal endoscopic surgery for anterior cranial base tumors. A retrospective chart review was conducted on patients who underwent an exclusive expanded transnasal approach to the anterior skull base in the period from December 2014 to November 2015. Data on patient demographics, tumor characteristics, surgical information, imaging, and postoperative complications were collected and analyzed. From a total of 120 patients with skull base diseases managed by the skull base team, 36 were admitted to this study. The overall complication rate in this series was 16.7%, gross total resection was achieved in 32 cases (88.9%) and postoperative CSF leakage occurred in 5 cases (13.9%). Our preliminary results confirm that an exclusive endoscopic transnasal approach to the anterior cranial base is a reliable technique with acceptable perioperative morbidity. Abstract : Supplemental Digital Content is available in the text